The structure of MgF 2 -WO 2 ceramic synthesized in a powerful electron flow - Мусаханов, Д; Лисицын, В; Карипбаев, Ж; Алпысова, Г; Голковский, М; Даулетбекова, А; Козловский, А; Здоровец, М (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article presents the results of a study of ceramics based on tungsten-activated MgF 2 ions synthesized in an air atmosphere. Samples were prepared using a powerful electron stream as a heater. The elemental composition of the obtained samples and the state of their surface were studied using a scanning electron microscope; as a result, it was found that the surface of the sample has a complex shape characteristic of a solidified melt. On some samples, microcrystals with sizes of about 500 nm formed with good faceting are visible. Studies of the distribution of elements over the surface of the samples were carried out, where it was found that the elemental composition noticeably differs when scanning over the surface. Using a diffractometer, an X-ray diffraction analysis of the synthesized ceramic samples was carried out, which showed the presence of a crystalline phase.